Targeted radionuclide therapy - Speer, Tod W. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Radioimmunotherapy, also known as systemic targeted radiation therapy, uses antibodies, antibody fragments, or compounds as carriers to guide radiation to the targets. It is a topic rapidly increasing in importance and success in treatment of cancer patients. This book represents a comprehensive amalgamation of the radiation physics, chemistry, radiobiology, tumor models, and clinical data for targeted radionuclide therapy. It outlines the current challenges and provides a glimpse at future directions. With significant advances in cell biology and molecular engineering, many targeting constructs are now available that will safely deliver these highly cytotoxic radionuclides in a targeted fashion"--Provided by publisher.
part I. Immunology and targeting constructs -- part II. The science of targeted radionuclide therapy -- part III. Tumor microenvironment and delivery strategies -- part IV. Unconjugated therapy -- part V. Conjugated therapy.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Cancer -- Radioimmunotherapy; Electronic books